2015
DOI: 10.1371/journal.ppat.1004999
|View full text |Cite
|
Sign up to set email alerts
|

THY-1 Cell Surface Antigen (CD90) Has an Important Role in the Initial Stage of Human Cytomegalovirus Infection

Abstract: Human cytomegalovirus (HCMV) infects about 50% of the US population, is the leading infectious cause of birth defects, and is considered the most important infectious agent in transplant recipients. The virus infects many cell types in vivo and in vitro. While previous studies have identified several cellular proteins that may function at early steps of infection in a cell type dependent manner, the mechanism of virus entry is still poorly understood. Using a computational biology approach, correlating gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 88 publications
3
47
0
Order By: Relevance
“…[38][39][40] CD90 has also been linked to HCMV entry, possibly through interaction with HCMV envelope associated glycoproteins. 41 Interestingly, HCMV infection strongly up-regulates expression of PDGFR and CD61, slightly increases CD90 but has no effect on CD29 or EGFR. HCMV-mediated PDGFR-a expression and activation has been shown to be essential for expression of viral genes, production of viral progeny and activation of signaling cascades.…”
Section: Discussionmentioning
confidence: 97%
“…[38][39][40] CD90 has also been linked to HCMV entry, possibly through interaction with HCMV envelope associated glycoproteins. 41 Interestingly, HCMV infection strongly up-regulates expression of PDGFR and CD61, slightly increases CD90 but has no effect on CD29 or EGFR. HCMV-mediated PDGFR-a expression and activation has been shown to be essential for expression of viral genes, production of viral progeny and activation of signaling cascades.…”
Section: Discussionmentioning
confidence: 97%
“…The involvement of integrins in Kaposi's sarcomaassociated herpesvirus (KSHV), Epstein-Barr virus (EBV), and herpes simplex virus (HSV) bolsters the evidence for involvement of these proteins in CMV infection (64)(65)(66)(67)(68). Recently, THY-1 (CD90) was identified as a putative entry factor that may form complexes with CMV gB and gH to link viral entry with signaling events that permit infection (69). A recent study by Wille et al demonstrated that CMV gB expressed on the cell surface could successfully complement infection by virions lacking the gB protein, arguing that gB is involved in fusion and is not required in a receptor-binding role in fibroblasts (70).…”
Section: Gb a Multifunctional Viral Glycoproteinmentioning
confidence: 99%
“…The more recently discovered gH/gL/ UL128/UL130/UL131A complex (Pentamer) instead is required for endothelial/epithelial cell, leukocyte, and monocyte tropism (26)(27)(28). On the cellular side, several putative HCMV receptors have been described, but none of them completely fulfills the characteristics of an entry receptor (17,29).…”
mentioning
confidence: 99%